BACKGROUND MATERIALS ON PRIVACY AND THE RIGHTS OF EMPLOYEES (Tufts Archival Research Center, 2007)
Marginalia; Report regarding the privacy rights of employees. Details many aspects of employee privacy including non-working hours activity, drug testing and smoking on and off the worksite. Includes several essays and articles on employee privacy. Lists state employee privacy laws and organizations and individuals concerned with privacy issues.